Connectedness to water as a predictor of household participation in water resources conservation in Singida municipality, Tanzania - Mulewi, Lunango G; Shitima, Mwivei; Utouh Harold M (African Journal of Empirical Research, 2024)
A research paper submitted to African Journal of Empirical Research, vol. 5. No.1of 2024, pg. 289-300.